Pregabalin as a perioperative strategy for pain management in patients undergoing cosmetic surgery. A randomized, double-blind, and placebo-controlled study - Chaparro Gómez, Luis Enrique; Valdés Cuartas, Paola; Mira Correa, Mauricio; Montoya Maya, Fernando; Duque, Lorena (Iatreia, 2008)
BACKGROUND: Preoperative Gabapentin has demonstrated to be as analgesic strategy in the control of perioperative pain. Pregabalin -an analogue of Gabapentin- has only a few trials demonstrating its effectiveness on this clinical setting. We wanted to assess the effectiveness of pregabalin given not only as a single dose in the preoperative period, but also continuing its administration 75 mg bid up to the fourth day after surgery.METHODS: Previous consent by the Ethical Committee of the University, we enrolled 110 patients undergoing ambulatory liposuction. They were randomized and blindedallocated to receive Pregabalin (75 mg bid) versus placebo, starting 12 hours before surgery up to the fourth day after surgery. We use the postoperative pain intensity by numerical rating scale, pain intensity by categorical pain scale and tramadol-ibuprofen request as primary outcomes.RESULTS: We had 9 dropouts during the recruitment and follow up. 24 hours after surgery we had 18/51 (35.3%) versus 16/50 (32%) (p=0.7). We also found no difference in opioid request at the same time point, being 6.3 mg morphine equivalents in the pregabalin versus 6.7 mg in the Placebo Group. Subsequent evaluations at 48, 72 and 96 hours demonstrated no difference between groups for analgesic request and pain intensity.CONCLUSION: Perioperative use of Pregabalin (75 mg bid) does not offer benefit as analgesic strategy in terms of pain intensity and opioid requirement in patients undergoing cosmetic liposuction.